Efeito da prensagem em canais equiangulares (ECAP) sobre a microestrutura e dureza do alumínio reciclado obtido em processos de usinagem - Santos, Eduardo de Oliveira (2023)
The present work investigated the influence of pressing in equiangular channels (ECAP) in commercial aluminum in the form of recycled chips, the material was compacted and melted through two molds made of carbon steel with different wall dimensions. Three ingots (pure Al, dry Al, traditional Al) were produced for each type of mold and a macrographic analysis was carried out. The 6 ingots gave rise to 36 specimens which were deformed with 2 ECAP passes using the Bc route and room temperature in a matrix with a core made of tool steel. After being deformed, the specimens were subjected to Vickers microhardness tests, optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction analysis (DRX) and finally, to compare the results, analysis of variance was performed, the ANOVA. The microhardness results showed a considerable increase in the hardness of the deformed material, confirmed by the SEM, where regions with intense deformation with elongated grains-subgrains were observed. XRD results showed peaks with lower and higher intensities related to the ECAP process in the deformed regions. The ANOVA compared the hardness results of the three types of aluminum produced by the two different dies and statistically significant differences were observed between the materials produced by the two dies, with the thick-walled die having better results for all aluminum conditions. The condition of traditional chip aluminum showed different hardness results in relation to dry chip aluminum and pure aluminum, the latter two showed satisfactory results, the averages for the thin wall die were 95.55 HV and for the wall die thick was 110.9 HV. The results indicated that dry machining recycled chips can be efficiently reused by applying suitable foundry processes associated with ECAP.